2016
DOI: 10.1016/j.brainres.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA synthase isoenzymes 1 and 2 localize to satellite glial cells in dorsal root ganglia and are differentially regulated by peripheral nerve injury

Abstract: In dorsal root ganglia (DRG), satellite glial cells (SGCs) tightly ensheathe the somata of primary sensory neurons to form functional sensory units. SGCs are identified by their flattened and irregular morphology and expression of a variety of specific marker proteins. In this report, we present evidence that the 3-hydroxy-3-methylglutaryl coenzyme A synthase isoenzymes 1 and 2 (HMGCS1 and HMGCS2) are abundantly expressed in SGCs. Immunolabeling with the validated antibodies revealed that both HMGCS1 and HMGCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 47 publications
7
39
0
Order By: Relevance
“…The observed downregulation of cholesterol biosynthesis thus seems to constitute part of a basic functional repertoire of activated SGCs. In keeping with our work, a previous study has reported the downregulation of the cholesterol synthesis enzyme ( Hmgcs1 ) in SGC after peripheral nerve injury (Wang et al, ), but the ultimate functional outcome of the multiple regulations we observed in the cholesterol synthesis pathway remains unknown. Studies on astrocytes—which also produce cholesterol–have suggested that astrocyte‐derived cholesterol is crucially important for neuronal health and synaptogenesis (Mauch et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed downregulation of cholesterol biosynthesis thus seems to constitute part of a basic functional repertoire of activated SGCs. In keeping with our work, a previous study has reported the downregulation of the cholesterol synthesis enzyme ( Hmgcs1 ) in SGC after peripheral nerve injury (Wang et al, ), but the ultimate functional outcome of the multiple regulations we observed in the cholesterol synthesis pathway remains unknown. Studies on astrocytes—which also produce cholesterol–have suggested that astrocyte‐derived cholesterol is crucially important for neuronal health and synaptogenesis (Mauch et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, we did not find mRNA expression of GFAP in either naïve SGCs, sham SGCs or injured SGCs (Table and File S1), and we could not detect any basal or elevated GFAP levels by IHC (data not shown). While GFAP seems to be robustly upregulated in SGC following nerve injury in rats (Christie et al, ; Donegan et al, ; Krishnan, Bhavanam, & Zochodne, ; Muratori et al, ; Nadeau et al, ; Obata et al, , ; Pavel, Oroszova, Hricova, & Lukacova, ; Wang et al, ; Woodham et al, ; Zhou et al, ; Zhou, Rush, & McLachlan, ; Zhuang, Gerner, Woolf, & Ji, ), our finding is consistent with recent studies unable to detect GFAP expression in naïve murine SGCs at single‐cell level (Zeisel et al, ) as well as after sciatic nerve injury (Carlin, Halevi, Ewan, Moore, & Cavalli, ). It is thus possible that there may be a hitherto unappreciated species difference between rats and mice, and further studies are required to explain the discrepancy in findings for this widely utilized molecular marker gene.…”
Section: Discussionmentioning
confidence: 99%
“…A unique characteristic of DRG structure is that SGCs tightly ensheathe the somata of primary sensory neurons to form discrete anatomical and functional sensory units (Pannese, ; Wang et al, ). Bidirectional neuron–SGC communication plays an essential role in regulating afferent signaling (Huang, Gu, & Chen, ; Kim et al, ; Rozanski, Nath, Adams, & Stanley, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH was used as a loading control. Ratios of the band density of GFAP protein to the GAPDH were calculated, and the percent changes of GFAP in the sham and the injected DRG samples were normalized against the average of naïve samples Wang et al, 2016.…”
Section: Western Blottingmentioning
confidence: 99%
“…Several recent studies have shown that lipids enriched in these membrane microdomains are disrupted in neuropathic pain. For example, the expression of a key enzyme in cholesterol synthesis hydroxymethylglutaryl-CoA synthase 1 (HMGCS1), is downregulated within the DRG after spinal nerve injury ( Wang et al, 2016 ). Another study ( Patti et al, 2012 ) also identified the dysregulation of sphingolipids, another class of lipids co-enriched in cholesterol-rich membrane microdomains (reviewed in Bou Khalil et al, 2010 ) in the ipsilateral dorsal horn during chronic neuropathic pain.…”
Section: Scenario 2: Disruption Of Atp-mediated Panx1 Endocytosis In mentioning
confidence: 99%